Mechanism and application of Lactobacillus in type 2 diabetes-associated periodontitis - Chen, Sisi; Zhang, Yuhan (Frontiers in Public Health, 2023)
Type 2 diabetes mellitus (T2DM) accelerates the progression of periodontitis through diverse pathways. Abnormal immune responses, excessive activation of inflammation, increased levels of advanced glycation end-products and oxidative stress have defined roles in the pathophysiological process of T2DMassociated periodontitis. Furthermore , in the periodontium of diabetic individuals, high levels of advanced glycation end-products and glucose. Meanwhile, progress in microbiomics has revealed that dysbacteriosis caused by T2DM also contributes to the progression of periodontitis. Lactobacillus, owing to its fine-tuning function in the local microbiota, has sparked tremendous interest in this field. Accumulating research on Lactobacillus has detailed its beneficial role in both diabetes and oral diseases. Here, we summarize the newly discovered mechanisms underlying Lactobacillusmediated improvement of T2DM-associated periodontitis and propose the application of Lactobacillus in the clinic.